2013
DOI: 10.1007/s11262-013-0984-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of shorter than genome length episomal Banana streak OL virus like sequences isolated from banana in India

Abstract: Electron microscopy and sequencing of reverse transcriptase and ribonuclease H (RT/RNase H) region of Badnavirus genome from two banana cultivars: Poovan (triploid: AAB) and Safed velchi (diploid: AB), exhibiting leaf streak symptoms, confirmed the association of Banana streak OL virus (BSOLV). As per ICTV species demarcation threshold of 80 % identity in RT/RNase H region, both the isolates were identified as BSOLV. Rolling circle and end-to-end amplification showed the association of two short episomal BSOLV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The amplification of badnavirus‐like sequences in many enset samples shows that badnavirus sequences are frequently integrated into the enset genome as is also the case for crops like banana, sugarcane, taro or yam (Baranwal et al., ; Geering et al., ; Harper, Osuji, Heslop‐Harrison, & Hull, ; Yang et al., ). A recent study on the complete enset genome (Harrison et al., ) demonstrated that the enset genome contains sequences of viral origin.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The amplification of badnavirus‐like sequences in many enset samples shows that badnavirus sequences are frequently integrated into the enset genome as is also the case for crops like banana, sugarcane, taro or yam (Baranwal et al., ; Geering et al., ; Harper, Osuji, Heslop‐Harrison, & Hull, ; Yang et al., ). A recent study on the complete enset genome (Harrison et al., ) demonstrated that the enset genome contains sequences of viral origin.…”
Section: Discussionmentioning
confidence: 93%
“…The occurrence of both full and deleted versions of a badnavirus genome has been described from Kalanchoë plants infected with Kalancho ë top‐spotting virus (Yang, Nicolaisen, Olszewski, & Lockhart, ). Recently, shorter‐than‐full‐length genomes of two replication competent isolates from Banana streak OL virus on banana have been reported from India (Baranwal, Sharma, Khurana, & Verma, ). Hence, it is possible that the deleted version of ELSV represents a DI‐DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Methodical way is different from other studies that most of them used PCR-based diagnostic method [3], [4], while bio-informatics and decision tree is used in this research [5]. Also, there are clear differences in a regard that we deal with precisely different types of banana streak viruses, such as Banana streak IM virus, Banana streak CA virus, Banana streak UM virus, etc.…”
Section: Introductionmentioning
confidence: 91%
“…It is the largest fruit crop in India, accounting 33% of the total fruit production, and has great socioeconomic significance. The crop is reported to be infected by a number of pests and diseases including a number of viruses such as Banana bunch top virus (BBTV) (Banerjee et al, 2014), Banana streak virus (BSV) (Baranwal et al, 2014), Cucumber mosaic virus (CMV) (Khan et al, 2011), Banana bract mosaic virus (BBrMV) (Balasubramanian and Selvarajan, 2014), Banana mild mosaic virus (BanMMV) (Teycheney et al, 2007), and Banana dieback virus (BDBV) (Hughes et al, 1998). Vegetative propagation of the banana crop results in continuation of viruses from one generation to the next generation, decreasing the yield of the products and the health of the plants.…”
Section: Introductionmentioning
confidence: 99%